Education Of The Elements That Influence Interest In A Career As A Tax Consultant - Angelica, Elniara; Hidayat, Vinny Stephanie (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study is to ascertain how financial rewards, labor market considerations, and workplace environment affect students' desire in pursuing careers as tax consultants. The whole student body of Maranatha Christian University's accounting program makes up the research population. In this study, thirty students make up the sample. Purposive sampling was the sample technique employed in this study, which employed explanatory research as its methodology. T Test and multiple regression analysis using SPSS are used in research hypothesis testing. The study's findings demonstrate that financial rewards have an impact on students' desire in pursuing careers as tax consultants. The work environment and labor market considerations have little bearing on a student's desire to become a tax consultant